Infection Control Practices in the Hemodialysis Units (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2021)
Infection control practice is a very crucial factor in the healthcare industry. Healthcare workers are given opportunities to grow and boost their knowledge on infection control through seminars, training programs, conferences, and conventions both locally and internationally. Implementation of learned knowledge through practices comes next to strengthen current policies and guidelines. This study investigated the knowledge on infection control of 42 healthcare workers working in six private dialysis centers in La Union. The study used a descriptive-developmental research design. The validity of the self-made questionnaire was computed using Cronbach Alpha had a value of 0.822. Approval of the Ethics Review Board (ERB) was sought before the conduct of the study to ensure that the study is in accordance with the guidelines and principles outlined in the Research Ethics Code. The data gathered was treated using descriptive and inferential statistics, while a Post Hoc Analysis was done for variables that showed significant differences. The findings showed that respondent healthcare workers, 1) are very highly knowledgeable in all areas of infection control and always practiced infection control measures and standards. 2) There is a significant difference in the level of knowledge and practice on infection control between the three groups of respondents; 3) there is a significant relationship between knowledge and practice on infection control. The healthcare workers in the dialysis unit know the proper means of waste disposal and segregation of wastes. However, some dialysis centers have limited supplies and lack auditing tools. There are significant differences among the healthcare workers due to a lack of proper training and knowledge. In addition, there are noted a significant difference in the level of knowledge and practices on infection control.
Keywords: Infection control, knowledge, healthcare workers